PENGARUH OPERATING CASH FLOW, OPERATING CAPACITY, DAN RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS - Driani, Jelita; Mungniyati, Mungniyati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to analyze the factors influencing the occurrence of financial distress in companies. The factors analyzed in this study include operating cash flow, sales growth, operating capacity, profitability, liquidity, leverage, firm size, and managerial ownership. The study employs secondary data from manufacturing companies that have maintained a consistent listing on the Indonesia Stock Exchange (IDX) from 2020 to 2023, concentrating on the years 2021 to 2023. The study employs multiple linear regression analysis and is processed using the Statistical Package for the Social Sciences (SPSS) software.The results of this study indicate that the factors affecting financial distress are operating cash flow, operating capacity, profitability, and liquidity. In contrast, sales growth, leverage, firm size, and managerial ownership do not have a significant impact on financial distress.